The potential of Endophytic Fungal Extract Isolated from Cinnamon (Cinnamomum burmannii) as Antidiabetic and Antioxidant - Eris Septiana; Fauzy Rachman; Yatri Hapsari; Yadi Yadi; Bustanussalam Bustanussalam; Siti Irma Rahmawati; Fauzia Nurul izzati; Partomuan Simanjuntak (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
An increase in blood glucose levels in people with diabetes can cause an increase in free radicals, which can worsen the disease. Thus, drugs that have antidiabetic and antioxidant activities are needed. The cinnamon plant is high in antioxidants and has long been used as a source for a diabetes drug. The utilization of endophytic fungi isolated from cinnamon plants as antidiabetic and antioxidant has never been reported. This study aims to investigate the antidiabetic as well as antioxidant activity from the extract of endophytic fungi from the cinnamon plant. The antidiabetic activity was tested using the α-glucosidase enzyme inhibition method, while antioxidant activity was tested using the DPPH free radical scavenging method. Total phenol content was measured based on the Follin-Ciocalteu reagent reaction. All endophytic fungal extracts from the cinnamon leaves, twigs, flowers, and fruit have antidiabetic and antioxidant activity as well as high total phenol content. The three parameters measured showed a positive correlation. Endophytic fungal extract of Cb.D6 isolate derived from the leaf had the highest antidiabetic and antioxidant activity among the other isolates amounting to 92.41% and 90.28%, respectively. In addition, the total phenol content of Cb.D6 isolates was also the highest with 357.83 mg equivalent to gallic acid/g extract. Therefore, the endophytic fungal extract of Cb.D6 isolate has the potential to be developed as a source of the antidiabetic and antioxidant ingredients.